Carbon Monoxide Modulation of Microglia-Neuron Communication - Soares, Nuno L. (2022)
This work was financed by FEDER-Fundo Europeu de Desenvolvimento Regional funds through the COMPETE 2020-Operational Programme for Competitiveness and Internationalization (POCI), Portugal 2020, and by Portuguese funds through FCT-Fundação para a Ciência e a Tecnologia/Ministério da Ciência (FCT), Tecnologia e Ensino Superior in the framework of FCT-ANR/NEU-NMC/0022/2012 grant, PTDC/MEC-NEU/28750/2017 grant, Applied Molecular Biosciences Unit-UCIBIO (UID/Multi/04378/2019) grant; LA/P/0140/2020 of the Associate Laboratory Institute for Health and Bioeconomy; and FCT provided individual financial support to NLS (PD/BD/127819/2016), BFM (PD/BD/128336/2017) and HLAV (IF/00185/2012).